LIQUEFACTION POTENTIAL AT PADANG CITY: A COMPARISON OF PREDICTED AND OBSERVED LIQUEFACTIONS DURING THE 2009 PADANG EARTHQUAKE - Adrin Tohari; Khori Sugianti; Eko Soebowo (JURNAL RISET GEOLOGI DAN PERTAMBANGAN, 2011)
ABSTRACT The September 30, 2009 Padang earthquake has resulted in damages to infrastructures and buildings and a death toll of 383 in Padang City. Numerous liquefaction and ground deformations caused by the earthquake were particularly evidence in the areas few kilometers from the coast. The paper presents results of the previous field geotechnical investigations of liquefaction potential and the recent liquefaction observations in Padang City. A microzonation map was created using the data from liquefaction potential analyses and liquefaction potential indexes. The predicted liquefaction susceptibility zones showed a good agreement with site observations. The assessment suggests that the liquefaction susceptibility decreases to the northeast away from the coastal line.